A new rod-shaped BODIPY-acetylene molecule for solution-processed semiconducting microribbons in n-channel organic field-effect transistors. (14th June 2017) - Ozdemir, Mehmet; Choi, Donghee; Zorlu, Yunus; Cosut, Bunyemin; Kim, Hyungsug; Kim, Choongik; Usta, Hakan
Abstract : A novel solution-processable BODIPY-based small molecule (BDY-PhAc-BDY ) yields highly-crystalline, one-dimensional (1-D) microribbon semiconductors for organic field-effect transistors (OFETs). Abstract : BODIPY-based π-conjugated small molecules have been extensively studied in various fields of sensing and biochemical labelling; however, their use in organic optoelectronic applications is very limited. A new solution-processable acceptor–donor–acceptor (A–D–A) type small molecule, BDY-PhAc-BDY, consisting of BODIPY π-acceptors and a rod-shaped 1, 4-bis-(thienylethynyl)2, 5-dialkoxybenzene π-donor, has been synthesized and fully characterized as a novel n-channel semiconductor in bottom-gate/top-contact organic field-effect transistors (OFETs). The new semiconductor exhibits an electrochemical band gap of 2.12 eV with highly stabilized HOMO/LUMO energy levels of −5.68 eV/−3.56 eV. Single-crystal X-ray diffraction (XRD) analysis ofBDY-PhAc-BDY reveals a relatively low "BODIPY- meso -thiophene" dihedral angle ( θ = 44.94°), antiparallel π-stacked BODIPY dimers with an interplanar distance of 3.93 Å, and strong "C–H⋯π (2.85 Å)" interactions. The OFET devices fabricated by solution processing show the formation of highly-crystalline, one-dimensional (1-D) microribbons, which results in clear n-channel semiconductivity with an electron mobility of 0.004 cm 2 V −1 s −1 and an on/off current ratio of 10 5 –10 6 . To date, this is the highest reported for BODIPY-based small molecular semiconductors with alkyne linkages. Our results clearly demonstrate that BODIPY is an effective π-acceptor unit for the design of solution-processable, electron-transporting organic semiconductors and easily fabricable 1-D semiconductor micro-/nano-structures for fundamental/applied research in organic optoelectronics.